Isle of Man : Financial Sector Assessment Program Update-Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents a Detailed Assessment of the Isle of Man's (IOM) Observance of the Basel Core Principles for the Effective Banking Supervision Report. The recent global financial markets turmoil has had a significant impact on the Manx financial system. The IOM has a deposit protection scheme, which has been amended shortly after the time of the assessment. The Financial Supervision Commission has adequate powers to ensure compliance with its regulations and other orders, and it uses these powers when the occasion demands.